Pembuatan Alat Hydraulic Hot Press sebagai Teknologi Tepat Guna dalam Pencetakan Totebag dari Lembaran Pelepah Pinang - Muslimah; Kiki Kristiandi; Nuria; Ety Astuti; Novita (Jurnal Engine: Energi, Manufaktur, dan Material, 2025)
The purpose of this study is to describe the process and results of developing a Hydraulic Hot Press machine for molding areca palm sheath sheets into tote bags. Areca palm sheaths were selected as the sample material due to their abundance as organic waste in Sambas Regency, which has not yet been utilized in waste processing. This research was conducted through five stages: literature review, tool design, preparation of tools and materials, fabrication, and testing. The development process of the Hydraulic Hot Press included determining the dimensions, constructing the frame, assembling the heating system, and conducting functional tests. The press was designed with dimensions of 100 cm in length, 60 cm in width, and 130 cm in height. It was equipped with a heating system powered by an LPG gas cylinder as the main energy source, with heat delivered through a piping system to the main pressing point. The results indicated that when the steel base plate of the press was subjected to hydraulic pressure and direct heating, thermal expansion occurred, causing slight bending of the steel foundation. This condition led to less-than-optimal molding results of the areca palm sheath sheets into tote bags.